Housing Production in Mid-Sized Cities: Local Building Contractors in Aydin - Kovankaya, Emre Irfan; Tuerkuen, Asuman (KARE PUBL, 2023)
This study examines the reflections of increase in housing pro-duction in Turkey in the 2000s and 2010s in medium-sized cities through development processes and behaviour patterns of small and medium-sized local contractors operating in Aydin. Housing production is one of the most important dynamics of change in urban space. Today, housing production is preferred as an in-vestment tool rather than its use value that will meet a basic need such as shelter and comes to the fore through its exchange value. In this study, housing production is handled in a context over exchange value rather than use value. In the literature, the post-1980 construction sector has been examined through mega projects, infrastructure investments, government policies, inter-nationalisation and large construction manufacturers, mainly in metropolitan cities. However, especially with the housing loan law enacted in 2007, construction production has also increased in medium-sized cities. This rise in the construction sector has been evident in the housing and real estate sectors. Medium and small housing producers in the expanding housing market in me-dium-sized cities continue to be influential on local scales, where large construction capital, which tends to centralize in housing production, does not deign to enter while trying to survive in the face of fluctuations and crisis trends in the market. This study examines the uniqueness of the housing sector in this region and the profiles of the housing manufacturers through the tendencies of the local building contractors active in the four settlements of Aydin province, namely Efeler, Kusadasi, Soke and Nazilli.
Keywords: Building contractors; housing production; constrcution industry; Public Administration